UPCRISPR: an ultrafast, one-tube multiplexed nucleic acid detection system for resolving the diagnostic gray zone in HPV16/18 detection - Linlin Bai; Dianwei Liu; Chunyan Qian; Weiqi Yuan; Kaiming Guo; Yao Wang; Feng Qian; Mingmin Shi; Bei Wang; Rui Wang (Analytica Chimica Acta, 2026)

Comparative metabolomics reveals distinct metabolic profiles and in vitro activities of fermented noni juice from Samoa and China's Hainan - Qianjin Ni; Meimei Nie; Linlin Han; Mingfei Gu; Lingming Xiong; Yayuan Xu; Lei Feng; Liying Niu; Runqiang Yang; Dajing Li; Zhuqing Dai (Food Chemistry, 2026)

Moisture transport patterns over the Northeastern Tibetan Plateau revealed by tree-ring δ18O records - Kai Wang; Xiaohua Gou; Takeshi Nakatsuka; Yiran Zhang; Jiangzhou Feng; Linlin Gao; Tao Wang; Yang Deng; Zhen Li; Kaixuan Yang; Xuan Li; Chongshan Wang; et al. (Journal of Hydrology, 2026)

IGF1-IGF1R signaling in tumor-associated macrophages regulates extracellular matrix organization in BRAF inhibitor-targeted melanoma - Ya Luo; Linlin Liu; Xing Zhou; Jiao Yang; Min Tang; Wei Feng; Chunlan Du; Xiaobo Liu; Liu Yang; Fei Liu; Liqun Zhang (Molecular and Cellular Biochemistry, 2026)

Aurantio-Obtusin Attenuates Aβ-Induced Cognitive Impairment and Synaptic Dysfunction by Suppressing Neuroinflammation in Mice - Xueying Feng; Wei Yu; Song Guo; Yanyan Ji; Junhua Li; Ling Wang; Guolu Zhong; Shiyi Li; Linlin Niu; Danxin Zhu; Kan Zhou; Yehong Du (Journal of Neuroimmune Pharmacology, 2026)

Role of M1 macrophage-derived exosomes in infantile hemangioma regression via AMPK/SIRT1/PGC1α pathway - LinLin Yue; XiuWen Zheng; XiaoQiang Wen; Yong Zeng; Wei Peng; QianDuo Li; LinShan Zeng; JinPing Liu; Yu Wang; WenQing Fu; HaiJin Liu; Feng Chen (Molecular & Cellular Toxicology, 2026)

Interdecadal change in triggering effect of subtropical Indian Ocean dipole on tropical Indian Ocean dipole and the role of Southern annular mode - Junqiao Feng; Linlin Zhang; Fujun Wang (Climate Dynamics, 2026)

Phosphate-buffered saline as pH regulators for citrus postharvest handling water, maintain fruit quality by enhancing the phenylpropanoid metabolic pathway - Yanfei Zhu; Huan Liu; Yunxi Xiao; Zhiqiang Xiong; Ling Shen; Jiajun Tang; Zhifeng Zhu; Linlin Zhong; Rangwei Xu; Quan Sun; Feng Zhu; Yunjiang Cheng (Postharvest Biology and Technology, 2026)

Structural snapshots of plant-specific KCS6-CER2 complex reveal the elongation mechanism of very-long-chain fatty acids - Yang Wang; Haiyan Wang; Xianpeng Yang; Yujiao Qin; Rangwei Xu; Ting Liu; Chunmei Shi; Hongyan Zhang; Linlin Zhong; Xiaolu Qu; Feng Zhu; Xiuxin Deng; et al. (Molecular Plant, 2026)

Modified grafted starch flocculant for the treatment of coal chemical gasification gray water: Synergistic turbidity and hardness removal - Lixin Li; Sinan Liu; Fan Yang; Mingyu Han; Zilong Dong; Caiyu Sun; Linlin Huang; Zhichao Feng; Miyi Luo; Lizhi Tian (Journal of Water Process Engineering, 2026)

Triggering Effect of Indian Ocean Dipole on Subtropical Indian Ocean Dipole: Interdecadal Change and Modulation by Interdecadal Pacific Oscillation - Junqiao Feng; Linlin Zhang; Fujun Wang (International Journal of Climatology, 2026)
Based on observational and reanalysis datasets, this study examines the relationship between the tropical Indian Ocean Dipole (IOD) that matures in boreal autumn and the subsequent Subtropical Indian Ocean Dipole (SIOD) that occurs in the following boreal winter, as well as its interdecadal variability over 1960–2024. Results suggest that a significant correlation between IOD and SIOD only exists in 1979–2005. During this strong correlation period, an intense IOD can trigger a persistent meridional circulation and mid‐latitude Rossby wave train, maintaining an anomalous cyclone–anticyclone pair (CACP) over the subtropical Indian Ocean, with the cyclone in the west and the anticyclone in the east, ultimately leading to the development of SIOD via local air–sea coupling. In other periods, this relationship weakens and the described coupling pathway fails to establish. A key factor enabling this efficient cross‐seasonal linkage is the presence of sustained oceanic memory. Specifically, the sea surface temperature and subsurface heat anomalies associated with the IOD persist from boreal autumn into winter, providing a thermal precondition that interacts with the atmospheric circulation to eventually develop the SIOD. Further analysis indicates that this interdecadal variation is modulated by the Interdecadal Pacific Oscillation (IPO). Specifically, the positive phase of IPO strengthens the Indo–Pacific Walker circulation anomaly, reinforces the tropical–subtropical meridional pathway, and thereby enhances the IOD's triggering effect on SIOD. In contrast, the negative IPO phase suppresses this pathway. This study offers new mechanistic insights that advance our understanding of cross‐seasonal interactions in the Indian Ocean and contribute to improved climate predictions. Furthermore, it clarifies the importance of accounting for non‐stationarity in the climatic background for seasonal forecasting.

3-mercaptopropyltriethoxysilane modified zein electrospun membrane for ethylene removal and its application to banana preservation - Feng Xiao; Yimeng Zhang; Haoran Wang; Ji Wei; Linlin Li; Hualin Wang (Food Packaging and Shelf Life, 2026)

Impacts of different physics schemes on hurricane forecasting in the unified forecast system (UFS) - Linlin Pan; Kathryn Newman; Mrinal Biswas; Brianne Nelson; Bin Liu; Zhan Zhang; Xuejin Zhang; Shuanglong Jin; Zongpeng Song; Rui Hu; Shuanglei Feng; Bo Wang; et al. (Atmospheric Research, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Unlocking iron-chromium flow batteries: Conquering kinetics and crossover for affordable grid storage - Jiaxin Meng; Guozhen Zhang; Weizhai Bao; He Liu; Cong Guo; Jingfa Li; Feng Yu; Linlin Yang; Aishui Yu (Chemical Engineering Journal, 2026)

Comparison of PM2.5 Pollution during Heating and Non-Heating Periods in Northwest China: Chemical Characteristics, Secondary Contribution, and Regional Transport - Linlin Liang; Xinze Geng; Feng Lin; Xiaoru Liu; Liping Ma; Kun Li; Leixiang Wu; Chang Liu; Xuyan Liu; Hongbing Cheng; Yusi Liu (Journal of Meteorological Research, 2026)

Electronic structure tuning of Mn-based high-entropy spinel boosts benzene catalytic oxidation - Jiarui Chen; Xiaotong Li; Junjie Feng; Linlin Deng; Mingtai Li; Baojuan Dou; Feng Bin (Chemical Engineering Journal, 2026)

Spatio-temporal pattern and driving mechanism of the coupling coordination of human settlements systems - Xueming Li; Meishuo Du; Linlin Feng; Shenzhen Tian; Jun Yang (Journal of Geographical Sciences, 2026)

A Deep-Sea Multi-Sequence Sampling System Integrating In Situ Microbial Filtration with Rapid RNA Stabilization - Wei Bu; Yuan-Jie Chen; Jinhai Luo; Linlin Sun; Xiang Li; Xinyuan Gao; Yuanli Fang; Leisheng Tang; Jiaying Zhao; Jingchun Feng; Haocai Huang (Journal of Marine Science and Engineering, 2026)
Rapid depressurization and warming during recovery can trigger stress in deep-sea microbes and accelerate RNA degradation. We developed a remotely operated vehicle (ROV)-oriented multi-sequence microbial sampler for 2000 m sampling (20 MPa, 2 °C) that integrates in situ filtration with immediate RNAlater injection (an RNA stabilization reagent), collecting up to 12 samples per dive. A Dirichlet sampling–B-spline–SVM framework was used to optimize the cam profile of the sequence trigger for robust actuation under geometric constraints and realistic tolerances in both manufacturing and assembly. Relative to the baseline 3-4-5 motion law, the optimized design reduces nominal peak driving torque by ~18–20% and lowers the maximum torque under tolerance perturbations; tests show a further ~10–25% reduction using a SiC ball–ZrO2 block pair versus a MoS2-lubricated titanium pushrod–ZrO2 block pair. A Darcy–Forchheimer porous-media computational fluid dynamics (CFD) model predicts earlier clogging on the lower membrane and a fast-to-slow RNAlater displacement process; greater membrane resistance mismatch delays 95% displacement and increases RNAlater loss. Simulations and Rhodamine B tests suggest an RNAlater consumption of 0.9 L per parallel filter (one membrane per side), and 20 MPa chamber tests confirm stable operation and membrane retrieval.

Black phosphorus quantum dots regulate inflammation and neural stem cells differentiation via Notch1 signaling through cell adhesion - Lu Chen; Yongyuan Guo; Lusen Shi; Shiji Zhang; Linlin Jiang; Yong Chang; Haoran Liu; Zihang Wang; Na Li; Shiqing Feng (Chemical Engineering Journal, 2026)

Hydrodynamics, mixing performance and power consumption in horizontal millimeter-scale helical tube reactors: comprehensive experimental and numerical investigations across a wide range of centrifugal-to-gravitational acceleration ratio - Zhongyao Zhang; Yuanjie Wu; Xiaopeng Chen; Jiezhen Liang; Qianyun Tan; Chenghong Wu; Bo Feng; Denghan Luo; Linlin Wang (Chemical Engineering Journal, 2026)

Construction of temperature-responsive helical carbon nanofibers-based composites toward switchable microwave absorption - Yudi Li; Linlin Zhao; Wei Feng; Rongling Zhang; Xialong Cai; Zhiyong Chen; Hanjun Wei; Xulin Yang; Pan Wang; Giulio Cerullo; Nabil Kadhim Taieh; Fanbin Meng; et al. (Chemical Engineering Journal, 2025)

Nonlinear trajectory tracking control of UVMS with compositing fuzzy disturbance observer and robust state-dependent Riccati equation - Qirong Tang; Yuanjie Di; Tong Li; Yuanzhe Cui; Zongwu Xie; Linlin Feng; Min Yu (Ocean Engineering, 2025)

Seismic performance of rubberized concrete double-column piers confined by corrugated steel tubes - Linlin Zhang; Baodong Liu; Mingyang Feng; Haibo Sun; Changshun Hao (Engineering Structures, 2025)

Photocatalytic chitosan/hydroxypropyl methylcellulose-based multifunctional film incorporated with chlorophyll-TiO2@carbon sphere dual heterojunction and L-arginine for banana preservation - Haoran Wang; Wei Ji; Feng Xiao; Yewen Xiao; Linlin Li; Xia Shu; Hualin Wang; Jun Yin (Chemical Engineering Journal, 2025)

Atypical seasonal variability of the Kuroshio Current in 2018 - Fujun Wang; Linlin Zhang; Junqiao Feng; Qingye Wang; Dunxin Hu (Frontiers in Marine Science, 2025)
Introduction Using three moorings deployed at 122.7°E, 123°E, and 123.3°E along 18°N from January 2018 to May 2020, this study investigates the seasonal variability of the Kuroshio Current (KC). Methods Sensitive experiments were conducted with the Regional Ocean Modeling System (ROMS). Results In 2019, the KC exhibited a typical seasonal cycle, being relatively strong during spring, summer, and winter, with the weakest flow occurring in autumn. In contrast, the KC displayed an atypical seasonal cycle in 2018, characterized by two distinct intraseasonal intensification events in late September and early November. The ROMS experiments revealed that local winds within the region (120°E–125°E, 15°N–20°N) were the primary driver of this atypical cycle. During the two key periods, persistent negative wind stress curl anomalies east of the mooring stations induced integrated positive sea surface height anomalies and corresponding northward meridional velocity anomalies via geostrophic balance. Discussion In 2019, the wind stress curl anomaly phases reversed compared to 2018, leading to the absence of the two peaks observed in the previous year.

Mitochondrial modulators: the defenders - Emmanuel Makinde; Linlin Ma; George D. Mellick; Yunjiang Feng (Phytochemistry Letters, 2025)

Boosting dynamic NH3 adsorption performance of UiO-66 via amino-induced local polarization - Zimu Liu; Mingtai Li; Zitong Zhao; Yulong Yang; Linlin Deng; Baojuan Dou; Feng Bin (Journal of Environmental Chemical Engineering, 2025)

Seismic behavior of prefabricated-assembled frames with corrugated steel tube confined connections and piers: Experiments, numerical models, and design - Linlin Zhang; Baodong Liu; Mingyang Feng; Haibo Sun; Changshun Hao (Engineering Structures, 2025)

Constructing artificial interphase layer of polyoxovanadates with high oxidizability and reversibility to boost dendrite-free lithium metal anode - Yihai Song; Jiayuan Zhang; Chunhui Zhang; Linlin Fan; Jian Song; Yundong Cao; Yi Feng; Hong Liu; Guanggang Gao (Chemical Engineering Journal, 2025)

SIMPLE: A One-Pot RPA-Cas12b Method for Single Nucleotide Variations Identification with an Expanded Scope and Clinical Applications - Kaiming Guo; Yongkang Lai; Yiru Han; Linlin Bai; Ting Wang; Shengzhou Wang; Ziqin Zhang; Dianwei Liu; Yanju Chen; Jiulong Zhao; Yanan Pang; Feng Qian; et al. (Phenomics, 2025)

Promoting oxidation of high concentration CO via strong metal support interaction in unreduced Pt-based catalysts - Yulong Yang; Xiaokun Yi; Linlin Deng; Zitong Zhao; Zimu Liu; Mingtai Li; Baojuan Dou; Feng Bin (Journal of Environmental Chemical Engineering, 2025)

MVPCR: Multiplex Visual Detection Strategy Based on Ultrafast PCR for Point-of-Care Pathogens Detection Within 10 Min - Ziqin Zhang; Cui Wu; Linlin Bai; Kaiming Guo; Ting Wang; Dianwei Liu; Mingrui Zhu; Feng Qian; Fang Zhang; Rui Wang (Phenomics, 2025)

Spegazzinia menglaensis, A Novel Species of Didymosphaeriaceae from Air in China - Xingwen Dai; Linlin Fang; Tong Chen; Manyao Feng; Zefen Yu (Current Microbiology, 2025)

Development and validation of a prediction model for the depressive symptom risk in commercial airline pilots - Jie Zhang; Xuhua Chen; Lin Zhang; Haodong Qi; Erliang Zhang; Minzhi Chen; Yiran Wang; Yunfei Li; Yan Chen; Qingqing Duan; Feng Shi; Linlin Wang; et al. (EPMA Journal, 2025)

Current and future thermal effects and spatial optimization modelling of urban greenspace in megacity - Rundong Feng; Shenghe Liu; Fuyuan Wang; Bin Chen; Kaiyong Wang; Linlin Xu (Sustainable Cities and Society, 2025)

Rapid, green and semi-automated PT-μSPE for antidepressants analysis in urine and plasma using melt-blown polypropylene from disposable face masks as sorbent - Qianwei Li; Bowen Deng; Ru Feng; Di Chen; Linlin Hua (Sustainable Chemistry and Pharmacy, 2025)

Influence of atomic coordination on the activity of lattice oxygen and catalytic oxidation of toluene over regular Cu2O crystalline - Linlin Deng; Mingtai Li; Xin Gao; Xiaokun Yi; Yang Zhao; Yulong Yang; Zitong Zhao; Jiarui Chen; Baojuan Dou; Feng Bin (Journal of Hazardous Materials, 2025)

Contribution of mitochondria to postmortem muscle tenderization: a review - Feng Huang; Zhenjiang Ding; Jinsong Chen; Bing Guo; Linlin Wang; Chunmei Liu; Chunhui Zhang (Critical Reviews in Food Science and Nutrition, 2025)

BDNF-VGF Pathway Aggravates Incision Induced Acute Postoperative Pain via Upregulating the Neuroinflammation in Dorsal Root Ganglia - Wenjing Zhao; Lulin Ma; Daling Deng; Linlin Han; Feng Xu; Tianhao Zhang; Yafeng Wang; Shiqian Huang; Yuanyuan Ding; Shaofang Shu; Xiangdong Chen (Molecular Neurobiology, 2025)

Improving soil structure and function for continuous cropping of sweet melon using microalgae-based biological fertilizer - Linlin Yang; Xiaotong Song; Yanzhang Feng; Xiaoting Qiu; Xiaojun Yan; Roger Ruan; Pengfei Cheng (Algal Research, 2025)

Closed-loop recylcing of thermoset poly(vinylogous urethane) foams - Shihao Ji; Linlin Wang; Shengyu Feng; Lei Li (Chemical Engineering Journal, 2024)

Non-coding RNA notations, regulations and interactive resources - Mengwei Cheng; Yinhuan Zhu; Han Yu; Linlin Shao; Yiming Zhang; Lanxing Li; Haohong Tu; Luyao Xie; Haoyu Chao; Peijing Zhang; Saige Xin; Cong Feng; et al. (Functional & Integrative Genomics, 2024)

Characteristics of iron-sulfur metabolism and acid-producing microorganisms in groundwater contaminated by acid mine drainage in closed coal mines - Yanchang Huang; Ping Lu; Feng Zhang; Hao Chen; Wenliang Zhang; Linlin Lin; Hepeng Xu; Haoran Ding; Tianhang Cheng (Groundwater for Sustainable Development, 2024)

Intelligent multi-colorimetric cellulose acetate/cobalt-based metal-organic framework antibacterial film and its application to pork preservation - Qianlan Tao; Yewen Xiao; Xuan Hu; Huaiting Pang; Feng Xiao; Linlin Li; Minmin Chen; Hualin Wang (Food Packaging and Shelf Life, 2024)

Corrigendum to “Shear mechanism of RCS joints with whole column-section diaphragm” Eng Struct 315(2024), 118475 - Weijian Zhao; Yuchen Tao; Siyuan Feng; Linlin Yuan (Engineering Structures, 2024)

Shear mechanism of RCS joints with whole column-section diaphragm - Weijian Zhao; Yuchen Tao; Siyuan Feng; Linlin Yuan (Engineering Structures, 2024)

Constructing efficient lithium salt dissociation solid-state electrolytes with high conductivity and transference number of Li ions for stable all-solid-state lithium batteries - Zengcai Guo; Shimin Liao; Feng Li; Linlin Shi; Bihai Su; Jingbo Mu; Yanming Wang; Zhongkai Huang; Feng Xu; Chaowen Guan (Chemical Engineering Journal, 2024)

A novel multifunctional photocatalytic membrane based on ternary heterojunction TiO2@PDA@BiOBr for biochemical oily wastewater purification - Wei Ji; Yewen Xiao; Feng Xiao; Linlin Li; Minmin Chen; Hualin Wang (Chemical Engineering Journal, 2024)

Rice grain quality traits impacted by rice black-streaked dwarf virus disease - Yue Sun; Jiayuan Zhang; Linlin Du; Chenyang Li; Ying Lan; Tong Zhou; Xin Zhou; Baodong Wei; Feng Lin (Journal of Cereal Science, 2024)

A critical review of characteristics of domestic wastewater and key treatment techniques in Chinese villages - Jing Zhang; Yungeng Jiang; Heyu Zhang; Dan Feng; Hongling Bu; Linlin Li; Shaoyong Lu (Science of The Total Environment, 2024)

Influence of point bars on nitrogen transport and reaction in riparian zones - Xunchuan Song; Ying Liu; Defu Liu; Jinghong Feng; Linlin Li; Yongsheng Guo; Junxiong Luo; Weiping Jiang (Journal of Hydrology, 2024)

Recent progress in the antidegradation strategies of two-dimensional transition metal carbides (MXenes) - Ying Li; Yudi Li; Linlin Zhao; Siyu Chen; Siren Guo; Xulin Yang; Pan Wang; Kui Li; Fan Lei; Wei Feng; Zihao Mou; Hanjun Wei (Journal of Environmental Chemical Engineering, 2024)

Antimicrobial photodynamic inactivation pH-responsive films based on gelatin/chitosan incorporated with aloe-emodin - Linlin Li; Li Xia; Feng Xiao; Yewen Xiao; Wei Ji; Baocai Xu; Hualin Wang (Food Chemistry, 2024)

Determination of chloropropanol esters and glycidyl esters in instant noodles based on solid-phase microextraction with chitosan-β-cyclodextrin coated fiber - Linlin Bian; Xue Ge; Senwei Feng; Guangxuan Chen; Kefeng Li; Xu Wang (Food Chemistry, 2024)

Response of photosynthetic characteristics and antioxidant system in the leaves of safflower to NaCl and NaHCO3 - Linlin Song; Yongliang Yu; Hongzhi Chen; Yuwei Feng; Shuo Chen; Huihui Zhang; Haijia Zhou; Li Meng; Yue Wang (Plant Cell Reports, 2024)

Control of postharvest soft rot of green peppers by Bacillus subtilis through regulating ROS metabolism - Peipei Feng; Xiaoyun Zhang; Esa Abiso Godana; Guillaume Legrand Ngolong Ngea; Solairaj Dhanasekaran; Linlin Gao; Jun Li; Lina Zhao; Hongyin Zhang (Physiological and Molecular Plant Pathology, 2024)

A comprehensive “quality-quantity-activity” approach based on portable near-infrared spectrometer and membership function analysis to systematically evaluate spice quality: Cinnamomum cassia as an example - Ziwei Zou; Bingjian Guo; Yue Guo; Xiaolong Ma; Sanshan Luo; Linlin Feng; Ziping Pan; Lijun Deng; Shihan Pan; Jinbin Wei; Zhiheng Su (Food Chemistry, 2024)

Preparation of PEI/La2O3/Polypropylene fiber filter for household water purifiers and investigation of its phosphate reduction and bacterial control - Linlin Hao; Gewei Feng; Zengli Zhai; Mingxuan Li (Journal of Water Process Engineering, 2024)

Quantifying the environmental synergistic effect of cooling-air purification-carbon sequestration from urban forest in China - Rundong Feng; Shenghe Liu; Fuyuan Wang; Kaiyong Wang; Ping Gao; Linlin Xu (Journal of Cleaner Production, 2024)

Automatic identification of factor profiles can be achieved by improved machine learning model - Bo Xu; Junbo Huang; Yi Ge; Chun Zhang; Han Xu; Feng Wang; Huan Zhao; Linlin Zhang; Jinxing Liu; Yinchang Feng; Guoliang Shi (Atmospheric Environment, 2024)

Clinical epidemiology of adenovirus pneumonia among Chinese hospitalized children - Jiao Tian; Xinyu Wang; Qi Li; Linlin Zhang; Junhong Ai; Guoshuang Feng; Yueping Zeng; Ran Wang; Zhengde Xie (Archives of Microbiology, 2024)

Revealing the degrading-possibility of methyl red by two azoreductases of Anoxybacillus sp. PDR2 based on molecular docking - Shulin Zhang; Linlin Feng; Yanyan Han; Zihang Xu; Luhui Xu; Xuejiao An; Qinghua Zhang (Chemosphere, 2024)

Recent advances in enhanced technology of Cr(VI) bioreduction in aqueous condition: A review - Linlin Ma; Nan Chen; Chuanping Feng; Qing Yang (Chemosphere, 2024)

Tissue-specific distribution and bioaccumulation of perfluoroalkyl acids, isomers, alternatives, and precursors in citrus trees of contaminated fields: Implication for risk assessment - Zhaoyang Liu; Shun Liu; Feng Xiao; Andrew J. Sweetman; Qianqian Cui; Hao Guo; Jiayi Xu; Ziyao Luo; Mingxia Wang; Linlin Zhong; Jay Gan; Wenfeng Tan (Journal of Hazardous Materials, 2024)

Photocatalytic chitosan-based bactericidal films incorporated with WO3/AgBr/Ag and activated carbon for ethylene removal and application to banana preservation - Feng Xiao; Yewen Xiao; Wei Ji; Linlin Li; Yimeng Zhang; Minmin Chen; Hualin Wang (Carbohydrate Polymers, 2024)

Vertical distribution of intraseasonal variation signals in the Kuroshio Current source area during 2018–2020 - Haobo Gong; Fujun Wang; Feng Liu; Linlin Zhang; Dunxin Hu (Frontiers in Marine Science, 2024)
In the Kuroshio Current (KC) source area, intraseasonal variation (ISV) plays a significant role in dynamic oceanic processes. This study used data collected from three moorings (122.7°E, 123°E, 123.3°E) along 18°N from January 2018 to May 2020 to investigate the ISVs of meridional velocities. Notably, our findings reveal that the ISV above 200 m has a period of approximately 56 days and its intensity exhibits a gradual increase toward the west. For the 500–800 m depth interval, the ISV period is 73 days at 122.7°E/18°N and 60 days at 123.3°E/18°N. This discrepancy indicates that the ISVs have different vertical structures and frequencies at 122.7°E and 123.3°E along 18°N. In particular, at 122.7°E/18°N, the distinctiveness of two different periods of ISVs in surface and subsurface layers was more pronounced in 2018 than in 2019. The analyses of eddy kinetic energy distribution and eddy tracking indicate a connection between ISV in stratification and locally generated mesoscale eddies in the KC source area. Specifically, the stronger eddy activity in 2018, in contrast with that in 2019, correlates with a more pronounced ISV. Energy analysis demonstrates a distinct positivity in the baroclinic conversion rate (BC) in the surface layer (upper 200 m) of the KC source region, surpassing the absolute value of the barotropic conversion rate (BT). This finding indicates a notable shift of energy from eddy available potential energy to eddy kinetic energy, strengthening the high-frequency ISV signals in this area. In the subsurface layer, a strong negative BT is observed west of 122.8°E, with its absolute value exceeding the BC. This finding indicates that the energy is converted from eddy kinetic energy into mean kinetic energy, resulting in the appearance of the Luzon Undercurrent (LUC) at mooring station 122.7°E/18°N, characterized by a low frequency of ISV. Contrastingly, a positive BT plays a dominant role at 123.3°E/18°N, leading to the disappearance of the LUC amid an apparent presence of high-frequency ISV.

Comprehensive analyses of annexins in naked carp (Gymnocypris przewalskii) unveil their roles in saline-alkaline stress - Linlin A; Yujing Zhang; Baoke Xu; Haichen Zhang; Yixin Li; Le Wang; Jian Liang; Weiguo Zhou; Zhaohui Feng; Hong Zhang (Aquaculture, 2024)

Seismic behavior of embedded rubberized concrete-filled corrugated steel tube column-to-foundation connections: Experimental, numerical modelling, and design - Mingyang Feng; Baodong Liu; Linlin Zhang; Yaoyao Wang; Haibo Sun (Soil Dynamics and Earthquake Engineering, 2024)

Insight into the mechanisms of neuroendocrine toxicity induced by 6:2FTCA via thyroid hormone disruption - Linlin Wu; Jie Gu; Xinjie Duan; Feng Ge; Heyong Ye; Lingcan Kong; Wenwei Liu; Rong Gao; Jiandong Jiao; Huanhuan Chen; Guixiang Ji (Chemosphere, 2023)

Strategies for the coordinated control of particulate matter and carbon dioxide under multiple combined pollution conditions - Zhenyu Wang; Huan Zhao; Han Xu; Jie Li; Tong Ma; Linlin Zhang; Yinchang Feng; Guoliang Shi (Science of The Total Environment, 2023)

Hydrophobic electrospun membrane of peppermint oil loaded zein with coating of methyltriethoxysilane for active packaging - Li Xia; Linlin Li; Yewen Xiao; Feng Xiao; Wei Ji; Min Pang; Hualin Wang (Food Hydrocolloids, 2023)

Mechanism of adsorption of hazardous gases by MoTe2 monolayers modified with nanoclusters - Zhiyan Feng; Long Lin; Linlin Su; Donglin Pang; Pei Shi (Journal of Environmental Chemical Engineering, 2023)

An ultra-stable high entropy metal nitride for aerobic oxidative desulfurization and source recovery of aromatic sulfides from fuel oils - Peiwen Wu; Chang Deng; Penghui Liu; Feng Liu; Linlin Chen; Bangzhu Wang; Wenshuai Zhu; Chunming Xu (Chemical Engineering Journal, 2023)

Exploring the therapeutic mechanism of Banxia Xiexin Decoction in mild cognitive impairment and diabetes mellitus: a network pharmacology approach - Cong Li; Wei Yang; Yubo Meng; Lina Feng; Linlin Sun; Zhenghong Li; Xingfang Liu; Mingquan Li (Metabolic Brain Disease, 2023)

Manipulating electron redistribution induced by asymmetric coordination for electrocatalytic water oxidation at a high current density - Sheng Zhao; Feng Hu; Lijie Yin; Linlin Li; Shengjie Peng (Science Bulletin, 2023)

Hair Selenium of Residents in Keshan Disease Endemic and Non-endemic Regions in China - Yuehui Jia; Ruixiang Wang; Guijin Li; Chen Feng; Lei Qi; Yuanyuan Wang; Shengqi Su; Yuanjie Zou; Xu Liu; Yanan Wang; Yiyi Zhang; Linlin Du; et al. (Biological Trace Element Research, 2023)

Strategies for mapping protein hydrolysate profiles and pharmacokinetics based on non-targeted proteomics combining skyline-aided quantitative techniques - Shuying Mao; Wei Jin; Sisi Fu; Keanqi Liu; Feng Xu; Linlin Wu; Yexin Xu; Huizhu Yang; Huafang Liu; Guangji Wang; Yan Liang (Analytica Chimica Acta, 2023)

Estimation of urban-scale photovoltaic potential: A deep learning-based approach for constructing three-dimensional building models from optical remote sensing imagery - Longxu Yan; Rui Zhu; Mei-Po Kwan; Wei Luo; De Wang; Shangwu Zhang; Man Sing Wong; Linlin You; Bisheng Yang; Biyu Chen; Ling Feng (Sustainable Cities and Society, 2023)

Cloning and expression of the mitochondrial cytochrome c oxidase subunit II gene in Sitophilus zeamais and interaction mechanism with allyl isothiocyanate - Linlin Jiang; Yue Li; Weilin Shi; Wei Chen; Zhiqing Ma; Juntao Feng; Ahmed S. Hashem; Hua Wu (Pesticide Biochemistry and Physiology, 2023)

Nanophytoplankton and microphytoplankton in the western tropical Pacific Ocean: its community structure, cell size and carbon biomass - Wenzhuo Yan; Zhuo Chen; Linlin Zhang; Feng Wang; Guicheng Zhang; Jun Sun (Frontiers in Marine Science, 2023)
Phytoplankton, as a crucial component of the marine ecosystem, plays a fundamental role in global biogeochemical cycles. This study investigated the composition and distribution of phytoplankton in the western Tropical Pacific Ocean using the Utermöhl method and carbon volume conversion. We identified four primary groups of phytoplankton: dinoflagellates (181 species), diatoms (73 species), cyanobacteria (4 species), and chrysophyceae (2 species). The clustering analysis classified phytoplankton into four groups based on their composition, which were found to be closely related to ocean currents. Diatoms were highly abundant in areas influenced by current-seamount interaction. In contrast, areas with little influence from ocean currents were dominated by Trichodesmium . The majority of phytoplankton had an equivalent spherical diameter (ESD) of 2-12 μm, with a few exceeding 25 μm. Although nanophytoplankton (ESD = 2-20 µm) dominated cell abundance, microphytoplankton (ESD = 20-200 µm) contributed significantly to carbon biomass (792.295 mg m -3 ). This study yielded valuable insights into the distribution and composition of phytoplankton in the western tropical Pacific Ocean, shedding light on the relationship between species distribution and ocean currents. In addition, it provided fundamental information regarding cell size and carbon biomass within the region.

Environmental DNA metabarcoding reveals the influence of human activities on microeukaryotic plankton along the Chinese coastline - Zheng Zhang; Jiang Li; Hongjun Li; Linlin Wang; Yuqi Zhou; Shuzhen Li; Zhaojing Zhang; Kai Feng; Ye Deng (Water Research, 2023)

Development of SSR markers on the basis of the Panax notoginseng transcriptome for agronomic and biochemical trait association analyses - Linlin Su; Yingpeng Zhang; Ye Yang; Yuan Qu; Xiuming Cui; Feng Ge; Diqiu Liu (Journal of Applied Research on Medicinal and Aromatic Plants, 2023)

Long-term non-phosphorus application increased paddy methane emission by promoting organic acid and methanogen abundance in Tai Lake region, China - Chen Xu; Susu Shen; Beibei Zhou; Yuanyuan Feng; Zhu He; Linlin Shi; Yu Wang; Haihou Wang; Tripti Mishra; Lihong Xue (Science of The Total Environment, 2023)

Colorimetric active carboxymethyl chitosan/oxidized sodium alginate-Oxalis triangularis ssp. papilionacea anthocyanins film@gelatin/zein-linalool membrane for milk freshness monitoring and preservation - Linlin Li; Li Xia; Feng Xiao; Yewen Xiao; Lanhua Liu; Shaotong Jiang; Hualin Wang (Food Chemistry, 2023)

Ethylene-vinyl alcohol copolymer/gelatin/cellulose acetate bionic trilayer fibrous membrane for moisture-adjusting - Li Xia; Linlin Li; Yewen Xiao; Feng Xiao; Wei Ji; Shaotong Jiang; Hualin Wang (Carbohydrate Polymers, 2023)

Golden 2-like transcription factor contributes to the major QTL against rice black-streaked dwarf virus disease - Xuejuan Li; Feng Lin; Chenyang Li; Linlin Du; Zhiyang Liu; Wenjuan Shi; Jianying Lv; Xiaoyan Cao; Ying Lan; Yongjian Fan; Yijun Zhou; Tong Zhou (Theoretical and Applied Genetics, 2022)

Seasonal variability of the North Equatorial Current–Kuroshio Current–Mindanao Current based on observations - Fujun Wang; Linlin Zhang; Junqiao Feng; Dunxin Hu (Frontiers in Marine Science, 2022)
Utilizing the direct mooring observation along 130°E (10.5°N, 13°N, 15.5°N, and 18°N), 18°N (122.7°E, 123°E, and 123.3°E), and 8°N (127°E) and satellite data, the seasonal variabilities of the North Equatorial Current (NEC), Kuroshio Current (KC), and Mindanao Current (MC) were investigated. The southern part of the NEC along 130°E, the KC along 18°N, and the MC along 8°N featured similar seasonal cycles: that is, the currents were strong in spring and weak in autumn, while the KC along 18°N featured another peak in winter. Moreover, the seasonal phase of the NEC along 130°E was latitude-dependent; it advanced slightly from 10°N to 14°N and delayed poleward. The seasonal variabilities of the three currents were mainly controlled by local winds and Rossby waves via a geostrophic relationship, as the mooring observation was consistent with satellite data. The calculation shows that the local wind was dominant in the above mentioned in-phase areas (i.e., the southern part of the NEC, KC, and MC), while Rossby waves played an important role in the northern part of the NEC. The results indicate that the NEC–KC–MC system had the same zonal dynamics but different meridional dynamics across seasons.

Abnormal Level of Manganese, Iron, Iodine, and Selenium in the Hair of Children Living in Kashin–Beck Disease Endemic Areas - Feng’e Zhang; Cuiyan Wu; Pan Zhang; Xi Wang; Peilin Meng; Sijia Tan; Linlin Yuan; Xiong Guo (Biological Trace Element Research, 2022)

The Structure and Function of Microbial Community in Rhizospheric Soil of American Ginseng (Panax quinquefolius L.) Changed with Planting Years - Guozhong Chen; Ying Xue; Xin Yu; Chongwei Li; Yuping Hou; Hongwei Zhu; Linlin Jiang; Weibo Zheng; Zhibin Feng; Youzhi Li; Wenli Tang; Xiaoyu Zhao; et al. (Current Microbiology, 2022)

AlgaeMask: An Instance Segmentation Network for Floating Algae Detection - Xiaoliang Wang; Lei Wang; Liangyu Chen; Feng Zhang; Kuo Chen; Zhiwei Zhang; Yibo Zou; Linlin Zhao (Journal of Marine Science and Engineering, 2022)
Video surveillance on the offshore booster station and around the coast is a effective way to monitor floating macroalgae. Previous studies on floating algae detection are mainly based on traditional image segmentation methods. However, these algorithms cannot effectively solve the problem of extracting Ulva prolifra and Sargassum at different sizes and views. Recently, instance segmentation methods have achieved great success in computer vision applications. In this paper, based on the CenterMask network, a novel instance segmentation architecture named AlgaeMask is proposed for floating algae detection from the surveillance videos. To address the feature extraction ability of the network in the inter-dependencies for position and channel, we introduce a new OSA-V3 module with the dual-attention block, which consists of a position attention mechanism and channel attention mechanism. Meanwhile, scale-equalizing pyramid convolution is introduced to solve the problem of scale difference. Finally, we introduce the feature decoder module based on FCOS head and segmentation head to obtain the segmentation area of floating algae in each bounding box. The extensive experiment results show that the average precision of our AlgaeMask in the tasks of mask segmentation and box detection can reach 44.22% and 48.13%, respectively, which has 15.09% and 8.24% improvement over CenterMask. In addition, the AlgaeMask can meet the real-time requirements of floating algae detection.

Genomic analysis of a recombinant coxsackievirus A19 identified in Xinxiang, China, in 2019 - Liang Yi; Li Zhang; Linlin Feng; Xubo Luan; Qian Zhao; Pengwei Xu; Yinbiao Wang; Ling Tao; Weidong Wu (Archives of Virology, 2022)

Lower activity time constraint on the ore-controlling Erdaogou fault in the Qingchengzi orefield of the Liaodong Peninsula, NE China - Yan Zhao; Yuewen Feng; Peng Zhang; Linlin Kou; Zhongzhu Yang; Shenghui Li; Wei Wang (Acta Geochimica, 2022)

The lag effect of 24-year tobacco consumption on lung cancer mortality in Henan Province, China, 1992 to 2016 - Linlin Li; Jie Lu; Xin Dai; Li Ma; Chongjian Wang; Liyun Feng (Environmental Science and Pollution Research, 2022)

Warming reshaped the microbial hierarchical interactions - Yuqi Zhou; Baoyu Sun; Baohua Xie; Kai Feng; Zhaojing Zhang; Zheng Zhang; Shuzhen Li; Xiongfeng Du; Qi Zhang; Songsong Gu; Wen Song; Linlin Wang; et al. (Global Change Biology, 2021)
Global warming may alter microbially mediated ecosystem functions through reshaping of microbial diversity and modified microbial interactions. Here, we examined the effects of 5‐year experimental warming on different microbial hierarchical groups in a coastal nontidal soil ecosystem, including prokaryotes (i.e., bacteria and archaea), fungi, and Cercozoa, which is a widespread phylum of protists. Warming significantly altered the diversity and structure of prokaryotic and fungal communities in soil and additionally decreased the complexity of the prokaryotic network and fragmented the cercozoan network. By using the Inter‐Domain Ecological Network approach, the cross‐trophic interactions among prokaryotes, fungi, and Cercozoa were further investigated. Under warming, cercozoan–prokaryotic and fungal–prokaryotic bipartite networks were simplified, whereas the cercozoan–fungal network became slightly more complex. Despite simplification of the fungal–prokaryotic network, the strengthened synergistic interactions between saprotrophic fungi and certain prokaryotic groups, such as the Bacteroidetes, retained these phyla within the network under warming. In addition, the interactions within the fungal community were quite stable under warming conditions, which stabilized the interactions between fungi and prokaryotes or protists. Additionally, we found the microbial hierarchical interactions were affected by environmental stress (i.e., salinity and pH) and soil nutrients. Interestingly, the relevant microbial groups could respond to different soil properties under ambient conditions, whereas under warming these two groups tended to respond to similar soil properties, suggesting network hub species responded to certain environmental changes related to warming, and then transferred this response to their partners through trophic interactions. Finally, warming strengthened the network modules’ negative association with soil organic matters through some fungal hub species, which might trigger soil carbon loss in this ecosystem. Our study provides new insights into the response and feedback of microbial hierarchical interactions under warming scenario.

Black Soldier Fly (Hermetia illucens) Larvae Significantly Change the Microbial Community in Chicken Manure - Xingxiao Zhang; Junzhe Zhang; Linlin Jiang; Xin Yu; Hongwei Zhu; Jianlong Zhang; Zhibin Feng; Xiang Zhang; Guozhong Chen; Zhijian Zhang (Current Microbiology, 2021)

Enhanced mass transfer and service time of mesh Ti/Sb-SnO2 electrode for electro-catalytic oxidation of phenol - Linlin Huang; Da Li; Junfeng Liu; Lisha Yang; Changchao Dai; Nanqi Ren; Yujie Feng (Environmental Science and Pollution Research, 2020)

Instability in boundary layer between the North Equatorial Current and underlying zonal jets based on mooring observations - Fujun Wang; Junqiao Feng; Qingye Wang; Linlin Zhang; Shijian Hu; Dunxin Hu (Journal of Oceanology and Limnology, 2020)

Review on observational studies of western tropical Pacific Ocean circulation and climate - Dunxin Hu; Fan Wang; Janet Sprintall; Lixin Wu; Stephen Riser; Sophie Cravatte; Arnold Gordon; Linlin Zhang; Dake Chen; Hui Zhou; Kentaro Ando; Jianing Wang; et al. (Journal of Oceanology and Limnology, 2020)

Dynamic features of near-inertial oscillations in the Northwestern Pacific derived from mooring observations from 2015 to 2018 - Shijian Hu; Lingling Liu; Cong Guan; Linlin Zhang; Jianing Wang; Qingye Wang; Jie Ma; Fujun Wang; Fan Jia; Junqiao Feng; Xi Lu; Fan Wang; et al. (Journal of Oceanology and Limnology, 2020)

Controlled synchronization of prolactin/STAT5 and AKT1/mTOR in bovine mammary epithelial cells - Baosheng Wang; Linlin Shi; Jingjing Men; Qingzhang Li; Xiaoming Hou; Chunmei Wang; Feng Zhao (In Vitro Cellular & Developmental Biology - Animal, 2020)

Low shear stress damages endothelial function through STAT1 in endothelial cells (ECs) - Linlin Zhu; Feng Wang; Hongfeng Yang; Junjie Zhang; Shaoliang Chen (Journal of Physiology and Biochemistry, 2020)

A reverse-transcription loop-mediated isothermal amplification (RT-LAMP) assay for detecting the pathogen of maize rough dwarf disease in China - Linlin Du; Wenjuan Shi; Xuejuan Li; Ying Lan; Feng Sun; Yongjian Fan; Tong Zhou; Yijun Zhou (Australasian Plant Pathology, 2019)

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

Exploration of the key functional strains from an azo dye degradation microbial community by DGGE and high-throughput sequencing technology - Yan Chen; Lizhen Zhang; Linlin Feng; Guotao Chen; Yuanxiu Wang; Zhijun Zhai; Qinghua Zhang (Environmental Science and Pollution Research, 2019)

Effects of key species mud snail Bullacta exarata (Gastropoda) on oxygen and nutrient fluxes at the sediment-water interface in the Huanghe River Delta, China - Baoquan Li; Tjeerd J. Bouma; Quanchao Wang; Laura M. Soissons; Francesco Cozzoli; Guanghai Feng; Xiaojing Li; Zhengquan Zhou; Linlin Chen (Acta Oceanologica Sinica, 2019)

Ozonation catalyzed by iron- and/or manganese-supported granular activated carbons for the treatment of phenol - Wei Xiong; Nan Chen; Chuanping Feng; Yang Liu; Ningping Ma; Jian Deng; Linlin Xing; Yu Gao (Environmental Science and Pollution Research, 2019)

Seismic behavior of breakwaters on complex ground by numerical tests: Liquefaction and post liquefaction ground settlements - Linlin Gu; Feng Zhang; Xiaohua Bao; Zhenming Shi; Guanlin Ye; Xianzhang Ling (Earthquake Engineering and Engineering Vibration, 2018)

Settlement mechanism of piled-raft foundation due to cyclic train loads and its countermeasure - Linlin Gu; Guanlin Ye; Zhen Wang; Xianzhang Ling; Feng Zhang (Earthquake Engineering and Engineering Vibration, 2017)

Effect of LA on the Growth and Development of the Main Organs in Female Mice - Xiuyuan He; Feng Lin; Yongtao Li; Yuxia Chen; Jing Li; Linlin Guo; Xuelei Han; Huan Song (Biological Trace Element Research, 2017)

A novel short anionic antibacterial peptide isolated from the skin of Xenopus laevis with broad antibacterial activity and inhibitory activity against breast cancer cell - Siming Li; Linlin Hao; Wanguo Bao; Ping Zhang; Dan Su; Yunyun Cheng; Linyan Nie; Gang Wang; Feng Hou; Yang Yang (Archives of Microbiology, 2016)

Expression of HIV-encoded microRNA-TAR and its inhibitory effect on viral replication in human primary macrophages - Li Li; Haimin Feng; Qin Da; Honglin Jiang; Lang Chen; Linlin Xie; Qiuling Huang; Hairong Xiong; Fan Luo; Lei Kang; Yan Zeng; Haitao Hu; et al. (Archives of Virology, 2016)

Oxidative stress promotes d-GalN/LPS-induced acute hepatotoxicity by increasing glycogen synthase kinase 3β activity - Linlin Wei; Feng Ren; Xiangying Zhang; Tao Wen; Hongbo Shi; Sujun Zheng; Jing Zhang; Yu Chen; Yuanping Han; Zhongping Duan (Inflammation Research, 2014)

Fibronectin and asialoglyprotein receptor mediate hepatitis B surface antigen binding to the cell surface - Jing Yang; Feng Wang; Linlin Tian; Jing Su; Xiangqian Zhu; Li Lin; Xiaoran Ding; Xuejun Wang; Shengqi Wang (Archives of Virology, 2010)

Increased expression of CDK11p58 and cyclin D3 following spinal cord injury in rats - Yuhong Ji; Feng Xiao; Linlin Sun; Jing Qin; Shuxian Shi; Junling Yang; Yonghua Liu; Dan Zhou; Jian Zhao; Aiguo Shen (Molecular and Cellular Biochemistry, 2008)

Lipopolysaccharide-Induced Upregulation of Tumor Necrosis Factor-α (TNF-α) and TNF Receptors in Rat Sciatic Nerve - Youhua Wang; Dan Zhou; Qin Shen; Chun Cheng; Hai-ou Liu; Yongwei Qin; Linlin Sun; Feng Xiao; Jian Zhao; Aiguo Shen (Journal of Molecular Neuroscience, 2007)